PENGARUH PERSEPSI DAN KOMPETENSI AKUNTAN PUBLIK DALAM PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP SISTEM INFORMASI AKUNTANSI AKURAT DI MASA PANDEMI COVID-19 - Geya Adiptadaniar; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the effect of public accountants' perceptions on the use of information technology and the competence of public accountants in the use of information technology on accurate accounting information systems during the Covid-19 pandemic. The sample of 31 respondents from 33 questionnaires distributed to auditors who work at the Public Accounting Firm in Malang City. The analysis used in this research is a multiple linear regression model with SPSS analysis tool. The results showed that simultaneously the perceptions and competence of public accountants in the use of information technology had a significant effect on accurate accounting information systems during the Covid-19 pandemic. Whereas partially the public accountant's perception variable in the use of information technology had a positive and significant effect on accurate accounting information systems during the Covid-19 pandemic and the competency variables of public accountants in the use of information technology had a positive and significant effect on accurate accounting information systems during the Covid-19 pandemic. Keywords: Perceptions, competencies, public accountants, use of information technology, accurate accounting information systems during the Covid-19 pandemic.